2023
DOI: 10.14412/2074-2711-2023-1-36-42
|View full text |Cite
|
Sign up to set email alerts
|

Glioneuronal apoptosis and neuroinflammation in drug resistant temporal lobe epilepsy

Abstract: Изучение глионейронального апоптоза и нейровоспаления крайне важно для понимания причин развития эпилепсии. В настоящее время основное внимание уделяется нейрональному апоптозу и отдельным аспектам нейровоспаления, в то время как апоптоз глии остается малоизученным. Цель исследования -оценить нейрональный и глиальный апоптоз в сопряжении с нейровоспалением в области эпилептического очага у пациентов с фокальной фармакорезистентной эпилепсией (ФРЭ). Материал и методы. Изучены биоптаты коры и белого вещества вис… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…These changes include demyelination, rarefaction, and microcystic transformation of the neuropil, as well as neuronal devastation foci and atrophy of the temporal lobe cortex [13]. Reactive gliosis and neuroinflammation, which accompany neuronal damage, are also believed to contribute to the emergence of hyperexcitability foci [14]. Recent research has highlighted the critical role of glial cells (astrocytes, microglia, and oligodendrogliocytes) in various neurodegenerative diseases [15].…”
Section: Introductionmentioning
confidence: 99%
“…These changes include demyelination, rarefaction, and microcystic transformation of the neuropil, as well as neuronal devastation foci and atrophy of the temporal lobe cortex [13]. Reactive gliosis and neuroinflammation, which accompany neuronal damage, are also believed to contribute to the emergence of hyperexcitability foci [14]. Recent research has highlighted the critical role of glial cells (astrocytes, microglia, and oligodendrogliocytes) in various neurodegenerative diseases [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrastructural changes in oligodendrogliocytes in DRE have been less studied; however, it has been shown that cells are most susceptible to apoptotic death [25], with the formation of Lewy bodies in the cytoplasm.…”
Section: Glia and Fi Bersmentioning
confidence: 99%
“…Increased expression of apoptotic markers, such as caspase-3, has been implicated in the pathogenesis of epilepsy. 3 Autophagy is another essential cellular process that involves the degradation and recycling of cellular components to maintain homeostasis. In epilepsy, dysregulation of autophagy has been proposed as a contributing factor to the neurodegenerative changes associated with the disorder.…”
Section: Introductionmentioning
confidence: 99%